Respuestas

2013-09-14T22:46:57+02:00
Natu,
Vamos a resolver paso a paso
1)
2.(x - 1) > 3.(x - 1)
2x - 2 > 3x - 3
2x - 3x > - 3 + 2
        - x > -1                    x < 1
2)
- x + 3x - 1 > 5 + 4x
   2x - 1 > 4 + 4x
   2x - 4x > 4 + 1
        - 2x > 5
          2x < - 5                   x < - 5/2
3)
8.x2 - (- 1/4) = 33/4
8x^2 + 1/4 = 33/4
        8x^2 = (33 - 1)/4
        8x^2 = 32/4
        8x^2 = 8
          x^2 = 1                     x1 = -1     x2 = 1
4)
1/3.x + 4 = - 4.(x + 1/3)
x/3 + 4 = - 4x - 4/3
x/3 + 4x = - 4/3 - 4
x/3 + 12x/3 = - 4/3 - 12/3
(x + 12x)/3 = - (4 + 12)/3
          13x = - 16                     x = - 16/13
graciasssssssss
me podrias ayudar con 3x+menor2x-7